2022
DOI: 10.1108/s1569-37592022000109a001
|View full text |Cite
|
Sign up to set email alerts
|

Decentralised Finance and Cryptocurrency Activity in Africa

Abstract: This paper presents a discussion of decentralized finance in Africa. It presents some statistics and data on decentralized finance in Africa. Thereafter, the potential benefits, challenges and regulatory issues associated with decentralized finance in Africa are discussed. Recently, there has been an increase in the use of cryptocurrency, decentralized finance applications (dApps) and decentralized financial services (DeFi) in several countries. These innovations facilitate the delivery of financial services u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Investment in blockchain-based business solutions is growing exponentially, but the adoption of blockchain by businesses has been low, especially SMEs (Ozili, 2022; Asante Boakye et al ., 2023). The reasons are apparent as the novelty of the technology and its complexity, which is not easy to understand given the relatively lower technical capabilities of small firms.…”
Section: Thematic Analysismentioning
confidence: 99%
“…Investment in blockchain-based business solutions is growing exponentially, but the adoption of blockchain by businesses has been low, especially SMEs (Ozili, 2022; Asante Boakye et al ., 2023). The reasons are apparent as the novelty of the technology and its complexity, which is not easy to understand given the relatively lower technical capabilities of small firms.…”
Section: Thematic Analysismentioning
confidence: 99%
“…Developing African countries have been very flexible in adopting Blockchain projects, as recorded in the recent study on 'Decentralised Finance and Cryptocurrency Activity in Africa' (Ozili 2022). The values from Blockchain projects and new Metaverses do not have to be purely financial.…”
Section: Academic Literature Reviewmentioning
confidence: 99%
“…Several studies in the literature such as Ozcan (2021), Katona (2021), Chohan (2021), Ozili (2022b) and Schär (2021) showed that there is widespread interest in DeFi because of its potential to eliminate traditional financial intermediaries, improve access to financial services, increase financial inclusion, increase transaction speed, improve flexibility in smart contracts, increase privacy and transparency, enhance security, increase trust and increase efficiency in the form of reduction in overhead costs for banks. Yavin and Reardon (2021) showed that DeFi can revolutionize modern finance by making banking more accessible and more flexible in society.…”
Section: Literature Reviewmentioning
confidence: 99%